DISKRESI SEBAGAI KEBEBASAN BERTINDAK PEMERINTAH (Tinjauan Konseptual dan Empris) - Yusri Munaf (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2018)
The concept of discretion is the concept of power, in this case the power of government in the sense of narrow (bestuur). Discretion as a concept of power is power in a specific sense, not in the routine sense. The power of discretion here is the freedom of government action. Freedom here has a neutral understanding, which describes the existence of a power to choose various actions. This discussion aims to provide clarity on the concept of discretionary power in the administration of government that is still controversial from various aspects so that the concept of power of discretion is not only acceptable power, but also at the same time acceptable juridically and morally / ethically. The discussion is complemented by empirical aspects of the application of discretion to the implementation of local government in Indonesia. The central government guarantees the protection of discretionary regional heads to accelerate the development and welfare of the people. Ministry of Home Affairs, explains that there are now Law No. 23 of 2014 on Regional Government, and Law No. 30 of 2014 on Government Administration, which guarantees discretion by the regional head. In principle, Law No. 23 of 2014 and Law No. 30 of 2014 serve as guidelines for the regional head to innovate and undertake discretion without hesitation and fear. However, the government's discretionary powers must remain operative under a legal system of the rule of law. Under the prescriptions of the rule of law principle, the government's discretionary powers coexist with the rule of law principle, the power of government discretion coexists with the principle of responsible goverment.